2004
DOI: 10.5005/jcdp-5-3-108
|View full text |Cite
|
Sign up to set email alerts
|

Partial Spontaneous Bone Regeneration Subsequent to Mandibulectomy

Abstract: A case of spontaneus bone regeneration after mandibulectomy is presented. The patient was young and had a mandibular resection performed for a large fibroma. Only one of the condyles was preserved. Partial preservation of the periosteum may play an important role in rapid bone regeneration. In this case bone regeneration occurred only in mandibular regions where the periosteum could be preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…[ 3 , 4 , 18 ] The literature review in this study clarified that spontaneous regeneration of the mandible was usually observed in young and middle aged patients. [ 3 , 5 12 ] However, Okoturo et al suggested that increasing age might not imply a decrease in periosteal bone-regenerating potential, and the present case of this report supported that suggestion. [ 18 ] However, it is necessary to consider that the patient in this case had used bisphosphonates as treatment for bone metastasis from breast cancer.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…[ 3 , 4 , 18 ] The literature review in this study clarified that spontaneous regeneration of the mandible was usually observed in young and middle aged patients. [ 3 , 5 12 ] However, Okoturo et al suggested that increasing age might not imply a decrease in periosteal bone-regenerating potential, and the present case of this report supported that suggestion. [ 18 ] However, it is necessary to consider that the patient in this case had used bisphosphonates as treatment for bone metastasis from breast cancer.…”
Section: Discussionsupporting
confidence: 68%
“…Twenty four patients (15 males and 9 females) were included in this review (Table 1 ). [ 3 , 5 12 ] The youngest was 6 years’ old, and the oldest was 51 years’ old, and their mean age and standard deviation was 21.6 ± 12.9 years. [ 3 , 5 12 ] The most common disease associated with surgical procedures was ameloblastoma (12 patients).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These have almost always been the answer for the more complex of dento-alveolar and even extra-oral defects Though dental implants have been successful means of rehabilitating patients with tooth loss, studies reported in the literature on the success of osseointegration of implants in regenerated bone have been relatively few and none of them have been done in the Indian scenario. [1][2][3] The ultimate test of regenerated bone is its amenability to function normally. 4 Studies that describe osseointegration of implants in bone which is regenerated in large volume bony defects as in cases of cysts and tumors are few.…”
Section: Introductionmentioning
confidence: 99%